Called and Gifted: Charism and Catholic Social Teaching - Pfeil, Margaret R. (Horizons, 2007)
This essay explores the formulation of Catholic social teaching as a form of ministry structured in relation to charism. After situating the concept of charism theolgically, it addresses the significance of charism as an organizing principle for the ministry of Catholic social teaching, referring in particular to the experiences of Oswald von Nell-Breuning and Dorothy Day. Finally, it suggests a form of ecclesial participation, such as the retrieval of mystagogy, that would facilitate the free and full exercise of charisms by all those called and gifted to serve the church in the formulation of Catholic social teaching.